Declaring independence : why 1776 matters - Larson, Edward J. (Edward John) (W.W. Norton and Company, 2025)
On the 250th anniversary of American independence, with the history of our founding a political battleground, this study of the ideas and battlefield sacrifices of 1776 by a Pulitzer Prize-winning scholar could not be more timely.